Wedding Bellas – migrancy as a dispute to photographic traditions. Issue 1 (1st April 2016) - Milic, Nela
Wedding Bellas is a digital photography and oral history project that explores a wish to belong to the European borderscape. The photographs are the stories of twelve women who found themselves at a time when they refused to leave. Many have been rejected – by partners, by landlords, by employers – and many have been refused leave to remain in the United Kingdom by the state. The women displayed resilience and resourcefulness in the face of these rejections, sometimes all happening at once, and the burden of those denials made them escape to fantasy. Some opted for equally stable, rooted and good-looking 'Queen's subjects' – a lamp post, a tree, a traffic sign; London landmarks. The artwork presents the brides as physically connected to their rooted British fellows. The images show desperation and illusion as with a true wedding ceremony. The paradox of this loss of reality, due to the pressures of life circumstances, is portrayed in the photographs, questioning if the situation the women are in is imaginary – a concept shared by both the audience and the person in the picture. With the nexus of text and image, the project troubles the perception of refugees and asylum seekers in the United Kingdom today and the role that digital technology plays in that process. It deals with the question of mediation of migrancy through the historic visual representation and mnemonic depictions in photographs that are challenged by the interventions of the migrants themselves in that process.